Neglecting the neglected: the objective evidence of underfunding in rheumatic heart disease - Macleod, C; Bright, P; Steer, A; Kim, J; Mabey, D; Parks, T (Oxford University Press, 2019)
Background Despite the substantial global burden of disease, rheumatic heart disease research receives little funding globally. Methods Using data from the Global Burden of Disease Study and funding from the G-FINDER database, we propose a novel logarithmic disability neglect index (DNI) to describe disease burden using disability-adjusted life years relative to funding for 16 major tropical diseases. Results Across a range of diseases, rheumatic heart disease received the least funding relative to disease burden (DNI=3.83). Other diseases facing similar underfunding include cysticercosis (DNI=2.71) and soil-transmitted helminths (DNI=2.41). Conclusions Rheumatic heart disease remains severely underfunded relative to disease burden.